Pengaruh Penambahan Bawang Putih dan Lama Fermentasi Terhadap Mutu Mikrobiologis dan Organoleptik Bebontot - Antara, Nyoman Semadi; Partama, I Wayan Sweta; Wrasiati, Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 1 (2017), 2017)
Bebontot is one of fermented meat product produced in Bali island, Indonesia. Chopped pork and fat are mixed with spices and salt. The mixer are wrapped in spatha of areca tree (Areca catechu L.) and fermented for several days to produce bebontot. The research was conducted to find out the effects of garlic in bebontot formulation and fermentation time on the bebontot quality. The result showed that the addition of garlic could suppressed significantly the growth of Enterobacteriaceae and Staphylococcus aureus, but not for lactic acid bacteria (LAB) and micrococci bacteria. During fermentation all investigated bacteria were change where LAB increased and Enterobacteriacea and Staph. aureus decreased during process of fermentation. The organoleptic characteristicts of bebontot were influenced significantly by combination of both treatments.